Peran Guru Tpa Mengurangi Kecanduan Ponsel Untuk Anak Usia Dini Di Kelurahan Dusun Curup - Eka Yanuarti; Muhammad Yogi Ramadhan; Marwan Hakim; Devi Purnama Sari (Insititut Agama Islam Negeri (IAIN) Curup, 2021)
The purpose of this study was to determine the role of TPA teachers to reduce addiction to mobile phones for early childhood in Kelurahan Curup. This type of research is a qualitative study, using interview techniques, observation and documentation analysis. The results of this study are the role of TPA teachers to reduce mobile addiction for early childhood in the village of Curup First Village TPA teachers as role models ie TPA teachers teach with examples applied directly from the TPA teacher itself, Second TPA teachers as supervisors namely TPA teachers not only transferring knowledge but more than that is by guiding students guiding about morals and guiding in achieving learning goals in order to be achieved as it should, the three TPA teachers as Motivators namely TPA teachers must be motivators so that students are motivated to apply the materials described in daily life, the four TPA teachers as managers namely TPA teachers must be able to manage the learning atmosphere that is reviewed from various aspects such as models, strategies and learning methods so that the material delivered by the teacher can be understood by students, the models, strategies and methods applied are also must be seen da ri various aspects such as the age of students, culture and various other aspects.